Preparation and characterization of ZnTe thin films by SILAR method - Kale, S. S.; Mane, R. S.; Pathan, H. M.; Shaikh, A. V.; Joo, Oh-Shim; Han, Sung-Hwan (ELSEVIER SCIENCE BV, 2007)
Nanocrystalline zinc telluride (ZnTe) thin films were prepared by using successive ionic layer adsorption and reaction (SILAR) method from aqueous solutions of zinc sulfate and sodium telluride. The films were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray analysis and optical absorption measurement techniques. The synthesized ZnTe thin films were nanocrystalline with densely aggregated particles in nanometer scale and were free from the voids or cracks. The optical band gap energy of the film was found to be thickness dependent. The elemental chemical compositional stoichiometric analysis revealed good Zn:Te elemental ratio of 53:47. (c) 2006 Elsevier B.V. All rights reserved.